Isolated antro-pyloric metastatic mass from colonic carcinoma: A rare case presentation. (December 2018) - Ray, Samrat; Yadav, Amitabh; Jain, Sunila; Nundy, Samiran
Abstract: Metastatic tumors to stomach are extremely rare with very few cases being described so far in the surgical literature. Colonic tumors metastatic to stomach represent a rarer entity and present a surgical challenge for diagnosis and management to the clinician. We, hereby present a case of adenocarcinoma of transverse colon metastatic to stomach more than 6 years after the index malignancy, presenting clinically with features of gastric outlet obstruction. It was treated with open subtotal gastrectomy, with diagnosis being made on histopathologic examination using special immunochemical stains. Adjuvant treatment in the form of chemotherapy was given and follow up cross sectional imaging showed no evidence of residual disease so far. Highlights: Extreme rarity of this pathological entity. Diagnostic challenges faced in such a clinical scenario. Forming a very rare and interesting differential diagnosis of gastric outlet obstruction. First case reported to present 6 years after the index colonic primary.